Performance and Recovery of Turfgrasses Subjected to Drought and Traffic Stresses - R. Braun; D. Bremer; J. Hoyle; N. Bloedow (Kansas Agricultural Experiment Station Research Reports, 2017)
This study is an effort to determine effects of drought and traffic in turfgrasses. During a 41-day summer drought in 2015 and 2016, warm-season (C4) grasses were more affected by traffic than cool-season (C3) grasses when percent green cover and turf quality were measured. This was because the non-trafficked plots in C4 grasses maintained higher percent green cover and turf quality throughout the drought due to better drought-stress tolerance than the C3 grasses. Regardless of traffic treatment or mowing height, C4 grasses maintained higher percent green cover and visual turf quality than C3 grasses during drought and recovery periods. There was a larger separation between traffic treatments within the higher (rough) height compared to the lower (fairway) height. Overall, traffic application during a drought will have a negative and accelerated impact on the above-ground portion of turfgrass, which will vary due to turf species and mowing height.
Keywords: drought; water conservation; golf cart; traffic